River geometry responses resulting from hydrological changes in a partially urbanized watershed: an experimental study in Southern Brazil - Otávio Cristiano Montanher; Eduardo Souza de Morais; Bruna Caroline da Silva de Matos (Revista Brasileira de Geomorfologia, 2025)
: Impervious surfaces resulting from urbanization can increase peak flow magnitudes and affect the physical integrity of rivers, leading to alterations in channel morphometric parameters. This study investigates the relationship between cross-sectional morphometry and both drainage area size and the proportion of impervious surfaces. Ten cross-sections were analyzed within the Maringá Stream watershed, located in southern Brazil. This watershed, the largest in the municipality of Maringá (~90 km²), encompasses both urban and rural drainage areas. Morphometric parameters were obtained through field surveys, and geoprocessing techniques were employed to quantify drainage area size and impervious surface ratio. Significant univariate relationships were identified only between the width-to-depth ratio and depth, respectively, with drainage area size and impervious surface ratio. Multiple regression analysis demonstrated that width, channel capacity, and hydraulic radius had statistically significant coefficients with both explanatory variables. The findings suggest that the impervious surface ratio strongly influences fluvial morphometry, although hydraulic geometry is primarily governed by the combined effects of urbanization and drainage area size.